Գրիգոր Լուսաւորչի տեսիլքի օրացուցային խորհրդաբանութիւնը եւ Նիպպուրեան օրացոյցի առաջին ամիսը - Մարտոյեան, Գագիկ (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
В видении армянского святого Григория Просветителя описан небесный храм, на вершине которого первоначально была изображена куполообразная часть зодиакальной карты от Козерога до Овна, с 4 созвездиями. Три из них: Козерог, Водолей и Рыбы — зимние месяцы декабрь, январь и февраль. Четвер- тое созвездие, Овен, образующее вершину купола, — это первый месяц весны, где находится престол Бога Солнца и где он будет править до наступления следующей зимы. В христианской Армении роль Солнца была передана Иисусу Христу, которого в средние века считали Солнцем справедливости. Бог Солнца у армян был связан с идеей столпа. Хотя Григорий Просветитель использует аллегорию этого столба как «католической церкви», рассмотрение его видения показывает, что мы имеем дело с дохристианским пониманием небесной оси, отделяющей новый год от старого года. Эта ось является опорой небесного храма. образованного на созвездии Овна. Он же первый месяц весны, который связан с мировосприятием, связанным с обновлением Вселенной и пробуждением жизни. Идеи восстановления небесного храма и божественного престола совпадают с представлениями о первом месяце весны Ниппурского лунно — солнечнего календаря Шумера. The vision of Saint Gregory the Illuminator of Armenia described a heavenly temple, on top of which was originally depicted a dome-shaped portion of the zodiacal chart from Capricorn to Aries, with four constellations. Three of them: Capricorn, Aquarius and Pisces are the winter months of December, January and February. The fourth constellation, Aries, which forms the apex of the dome, is the first month of spring. It houses the throne of the Sun god, where he will rule until the next winter. In Christian Armenia, the role of the Sun was transferred to Jesus Christ, who was considered the Sun of Justice in the Middle Ages. The Armenian Sun god was associated with the idea of a pillar. Although St. Gregory the Illuminator uses an allegory of this pillar as the “Universal Church,” a consideration of his vision shows that we are dealing with a pre-Christian understanding of the celestial axis separating the new year from the old year. This axis is the support of the heavenly temple formed on the constellation Aries. It is also the first month of spring, which is associated with a worldview associated with the renewal of the universe and the awakening of life. The ideas of restoring the heavenly temple and the divine throne coincide with the ideas about the first month of spring of the Nippur lunisolar calendar of the Sumerians.
Keywords: Պատմություն; Տօմարագիտութիւն